BUILDING FINANCIAL BEHAVIOR THROUGH PARENTAL FINANCIAL TEACHING - Tifania Angga; I Gusti Bagus Yosia Wiryakusuma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research was conducted to explore the impact of financial teaching given by parents on financial attitudes and financial behavior in the younger generation living in Pekanbaru. This research used a sample of 100 young respondents in Pekanbaru. Apart from that, this research also uses the PLS-SEM approach which is used to evaluate the research hypothesis. According to the outcomes of this quantitative research, parental financial teaching affects children's financial behavior. In addition, parental financial teaching also has a significant impact on children's financial attitudes. It was also found that children's financial behavior was influenced by the child's financial attitudes. Then, it was found that children's financial attitudes were able to mediate the influence of parents' financial teaching on children's financial behavior.